Experimental and numerical studies on large-volume hoop-wrapped composite cylinders with steel liner under fire conditions. (October 2022) - Bo, Ke; Zheng, Jinyang; Zhao, Baodi; Liu, Cenfan; Liao, Binbin
Abstract: Tube trailer consisting of large-volume hoop-wrapped composite cylinders with steel liner (type II cylinder) has the advantages of light weight and large filling capacity. It is widely used for hydrogen storage and transportation in China. In order to ensure the safety of cylinders under fire exposure, fire tests are conducted for gas cylinders according to the ISO11515 standard. However, test data on the fire performance of type II cylinder are limited and the selection criteria of safety relief devices under fire exposure are unclear. In this paper, fire tests were carried out for the large-volume hoop-wrapped composite cylinder fitted with different pressure relief devices (PRDs). The temperature and pressure in the cylinders during fire tests were obtained. The temperature of PRD was measured by transducers. Besides, the response behaviors of the different PRDs (rupture disk structure and rupture disk–fusible alloy combined structure) in fire were compared. A computational fluid dynamics model was established to verify the experimental results. The results showed that the rupture disk structure generally actuated before the rupture disk–fusible alloy assembly structure for type II cylinder under fire exposure, manifesting that the rupture disk structure is a preferable PRD to be used with the large-volume type II cylinder on tube trailer. Highlights: The inner pressure and temperature law of large-volume type II cylinder in fire test was obtained. The fire-resistant time of large-volume hoop-wrapped composite cylinder is shorter than the TPRD activation time. The rupture disk is preferred as the safety relief device for the tube trailer because of higher probability of actuation.